Znaczenie pracy w życiu mieszkańców współczesnego miasta. Studium socjologiczne na przykładzie Katowic - Kasperek, Andrzej (Studia Etnologiczne i Antropologiczne, 2016)
The author of the very text aims to raise the issue of the relationship between work and function¬ing of a specific type of an industrial city gradually transforming into a postindustrial one as a result of socio cultural and economic changes. His considerations start from a draft presentation of the importance of a professional work, an emphasis being put on mine work in life of the inhabitants of Upper Silesia, starting from the period of an abrupt 19th century industrialization and urbanization. The author treats work as a par excellence cultural phenomenon, as an important element of the system of values at the same time organizing an everyday life of the inhabitants of cities in Upper Silesia. He also pays attention to the social motive of urban space creation, the organization of which was largely influenced by its adjustment to the professional work. An exemplification of the very issue constitute the results of survey studies conducted this year among the inhabitants of Katowice. Based on them, the author makes an attempt to evaluate the impor¬tance of work in life of the inhabitants of Katowice, the level of satisfaction from it, their conception of the so called “good job”. Also, he tries to answer the question on the extent to which contemporary Katowice satisfy the inhabitants’ expectations connected with the opportunities of finding a good job. The author attempt to combine these expectations with the satisfaction of other needs related to the sphere of non work (e.g. recreation). He finishes his considerations with a conclusion that mental changes, constituting a consequence of the socio cultural process and economic transformation of the region of Upper Silesia find their very tangible traces in the attempts to transform the urban space which, as the findings revealed, is perceived by a large number of respondents as devastated in many respects (e.g. when it comes to the possibilities of satisfying cultural needs or spending free time) whereas devastation remains a consequence of the industrial nature of the city.